A Can of Worms - Some Problems with the Development and Application of the Concept of Corporate Social Reporting - Woodward, David G (The International Journal of Accounting and Business Society, 1997)
lt is possible to evidence many problems within the area of corporate social reporting. These, it is proposed, explain why the topic has not made as much progress as many concemed individuals, both inside and outside the academic commuhity, would wish. The present paper attempts to identify the various problem areas by drawing on the literature and attempts some level of synthesis (partial, it is accepted, given the inherently complex nature of the whole concept of an organisation being responsible to society and then reporting on how that responsibility has been discharged). It is nevertheless concluded that further progress with the concept is possible. Recommendations are made as to how that progress might occur and the chances of success along the different dimensions assessed. lt is expected that progress will be both more substantial and more rapid in some areas than in others.